Constraints Impeding Livelihood Diversification of Farmers in Aspirational Districts of Bihar - Neha Singh, KS Kadian, Hans Ram Meena; Rahul Bellagi (Indian Journal of Dairy Science, 2024)
Farmers are facing a major problem of managing livelihood security because of changing environmental condition, globalization, changing economy, and the soil fertility that ultimately threatens our food, economic, infrastructure and social security in long term. The research was conducted on dairy farmers in selected district and the sampling technique has been done by multi-stage method, followed by Focus Group Discussion (FGD) and interview by questionnaire. To assess the constraints in achieving the livelihood security through different means of livelihood by farmers, the “Garrett Ranking Method” was used. The top most economic constraint as reported by the respondent was ‘High cost forbalance and nutricious food items’ with Garrett mean score of (61.29). Out of seven infrastructure constraints perceived by them, first rank was assigned to the “Poor or underdeveloped marketing infrastructure (mean score 63.80)”. Asymptotic significance was obtained from the Friedman test0.000 (p<0.01) with chi-square value of 22.803 and degrees of freedom of value 4.The diversification of livelihood sources can be grouped as agricultural farming, dairy farming, orchard plantations, poultry, and fisheries. In this study different constraints have been identified under sub-headings of economic constraints, infrastructure constraints, marketing constraints, technical constraints and communication constraints. These limiting factors (constraints) are global, comprehensive, integrated, and holistic and beyond the ability of farmers to manage them, thus there is a need for proactive problems-solving by the governmental intervention to overcome.